THE EFFECT OF CO2 THERAPY AND ITS COMBINATIONS ON INFLAMMATORY ACTIVITY AND IMMUNE STATUS: AN EXPERIMENTAL STUDY - Shtroblia, Viktor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Osteoarthritis (OA) is a chronic degenerative disease characterized by cartilage destruction, inflammation, and autoimmune processes. The limited effectiveness of current therapies has generated interest in alternative approaches, such as carboxytherapy, which possesses anti-inflammatory and regenerative properties. Objective. To evaluate the effects of carboxytherapy (CO2) in mono- and combination therapy on a carrageenan-induced model of inflammation in rats by assessing leukocyte differential counts and integral indices. Methods. The study was conducted o n 56 white rats divided i nto 7 groups (n = 8): control (intact and carrageenan-induced), mono- and combination therapy with CO2 in conjunction with diclofenac or chondroitin. Changes in the leukocyte differential counts and integral indices (NMR, NLR, LSI, LI, IIR) were evaluated. Results. CO2 monotherapy (Group V) reduced the NMR (Neutrophil-to-Monocyte Ratio) by 25.4 % (15.60 ± 2.95 vs. 20.92 ± 8.89 in Group II, p < 0.001). The Leukocyte Index (LI) increased by 82.2 % (1.471 ± 0.155 vs. 1.791 ± 0.191, p = 0.001). The combination of CO2 with diclofenac (Group VI) reduced NMR by 68.3 % (6.61 ± 2.72, p < 0.001) and increased LI by 103.1 % (3.637 ± 0.770, p < 0.001). CO2 combined with chondroitin (Group VII) reduced the NLR (Neutrophil-to-Lymphocyte Ratio) by 48.6 % (0.290 ± 0.0938, p < 0.001) and increased LI by 121.7 % (3.847 ± 1.421, p < 0.001). In Groups VI and VII, there was a significant decrease in band neutrophils (by 79.2 % and 75.0 %, respectively) and an increase in lymphocytes (by 72.2 % and 70.9 %, p < 0.001). Conclusions. Carboxytherapy modulates the inflammatory response and enhances the immune response. The best results were observed with combined CO2 therapy with diclofenac or chondroitin, confirming their potential in reducing inflammation and stimulating regeneration.